If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X * 1 + X = 0 Reorder the terms for easier multiplication: 1X + X = 0 Combine like terms: 1X + X = 2X 2X = 0 Solving 2X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Divide each side by '2'. X = 0 Simplifying X = 0
| 26=15+v | | c/5=-11/6 | | -15x+11x-3=1-5(x+1) | | 3(y+6)=2y-2 | | 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 | | y-94=5(x-9) | | -4p-13p-p=-150 | | 4y-14=30 | | 14*30+b=-192 | | y-2=5(x+3)fory | | y-9=5(x+8) | | 175+15d=250 |